Bhagavad Gita and Hinduism : what everyone should know - Nilesh M. Shukla (New Delhi : Readworthy, 2010)
This book explores the composition of a Hindu mindset, focusing on the essential knowledge everyone should have about the Bhagavad Gita and Hinduism.
Includes index.
Keywords: Bhagavadgita - Criticism, interpretation, etc; Bhagavadgita; Hinduism